Simulation and optimization of ethanol autothermal reformer for fuel cell applications - Adam, Muhamad Syafiq (2006)
Fuel cell application from hydrogen was one of alternative energy that being studied and widely accepted in industry. This case study focused on optimization of hydrogen production for fuel cell applications. In this case study, ethanol was chosen as a raw material and with autothermal reforming as a process of produce hydrogen. Using a commercial dynamic flow sheeting software, HYSYS 3.2, the process of hydrogen production was successfully simulated. In this research, fuel processor consists of an autothermal reactor, three water gas shift reactors and a preferential oxidation reactor was successfully developed. The purpose of this case study is to identify the effect of various operating parameters such as air-to-fuel (A/F) ratio and steam-to-fuel (S/F) ratio to get the optimum hydrogen production while made carbon monoxide lower than 10 ppm. From the results, an optimum A/F and S/F ratio are 5.5 and 1.5, respectively to produce 34 % of hydrogen and 10.055 ppm of CO. Under these optimum conditions, 83.6% of fuel processor efficiency was achieved.